2019
DOI: 10.1590/0004-282x20190028
|View full text |Cite
|
Sign up to set email alerts
|

Validation of multiplex PCR for the diagnosis of acute bacterial meningitis in culture negative cerebrospinal fluid

Abstract: This study evaluated the operational characteristics of the multiplex polymerase chain reaction (PCR) for cerebrospinal fluid (CSF) from patients with cellular and biochemical characteristics of acute bacterial meningitis and positive or negative CSF cultures. Methods: Multiplex PCR was performed for 36 CSF samples: culture-proven acute bacterial meningitis (n = 7), culture-negative acute bacterial meningitis (n = 17), lymphocytic meningitis (n = 8), and normal CSF (n = 4). The operational characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
3
5
0
1
Order By: Relevance
“… 5 FilmArray was shown to be efficatious in detecting bacterial etiology in meningitis cases in which CSF culture was negative. 6 , 7 A previous report showed rapid detection of Listeria monocytogenes in a patient in which CSF Gran stain and culture were negative, as occurred in a case in our series. 8 A large study showed high sensitivity and specificity levels.…”
supporting
confidence: 67%
“… 5 FilmArray was shown to be efficatious in detecting bacterial etiology in meningitis cases in which CSF culture was negative. 6 , 7 A previous report showed rapid detection of Listeria monocytogenes in a patient in which CSF Gran stain and culture were negative, as occurred in a case in our series. 8 A large study showed high sensitivity and specificity levels.…”
supporting
confidence: 67%
“…This difference in results was statistically significant (P < 0.05). complement to classical bacteriology techniques [29]. PCR showed in this study a significantly higher detection rate of bacterial meningitis when compared to culture, the confirmation rate was 33% by culture and 70% by RT-PCR.…”
Section: Discussionsupporting
confidence: 54%
“…qPCR has high sensitivity and specificity, and produces faster results because it does not require the previous growth of the microorganism. Multiplex qPCR of the cerebrospinal fluid (CSF) proved to be a valuable method for improving the rapidity and accuracy of a diagnosis of bacterial meningitis, even in cases with CSF culture-negative results [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time PCR is highly accurate in diagnosing meningitis caused by S . pneumoniae [ 4 , 5 , 7 ] and it also can be applied as a tool to detect antimicrobial resistance genes faster than the identification of phenotype by AST, especially in culture-negative samples.…”
Section: Introductionmentioning
confidence: 99%